Mapping the Role of Millet Mission in Localising SDGs: Evidence from the Indian States with Special Reference to Odisha - Bhatter, Mohit Kumar; Laha, Arindam (New Countryside, 2026)
Climate change is one of the biggest challenges of the twenty-first century, necessitating adaptation to climate resilient agricultural practices (e.g., millet cultivation) to withstand shocks. The Odisha Millet Mission (OMM) is a unique flagship programme launched by the Government of Odisha in 2017–2018 to improve the entire millet ecosystem from cultivation to consumption. In this context, this paper outlines the progress of the millet mission across Indian states, with special reference to Odisha. In addition, this paper assesses the role of OMM in localising the Sustainable Development Goals (SDGs) by mapping the outcomes of such a mission to the global targets using a structured qualitative SDG mapping framework (following the Food and Agriculture Organization (FAO)’s Climate Smart Agriculture-SDG framework). It finds that OMM contributes to the localisation of the major (directly influencing) and contributing (indirectly influencing) outcomes of the OMM initiative on achieving the SDG targets. In addition to advancing climate action (SDG 13), food security (SDG 2), and income objectives (SDG 1), a millet farming approach can contribute to priority goals, including gender equality and social equality (SDG 5), urban development, and employment (SDG 8). Therefore, these findings showcase the mission’s comprehensive approach to sustainably increase agricultural productivity and incomes (economic), reduce Greenhouse Gas (GHG) emissions, build resilience and adapt to climate change (environment) and empower disadvantaged people (social). Eventually, OMM will offer a scalable, best-practice guide for SDG localisation across other states to support millet revival, strengthen agrarian economies, and build adaptive capacity.